Toxicological efects and behavioural and biochemical responses of Oreochromis mossambicus gills and its cholinesterase to copper: a biomarker application - Ain Aqilah Basirun; Siti Aqlima Ahmad; Nur Adeela Yasid; Mohd Khalizan Sabullah; Hassan Hj Mohd Daud; Shakirah Sha’arani; Ariff Khalid; M. Y. Shukor (2018)
Gills are both morphologically and physiologically complex whereby they perform several functions such as gas exchange, ion and water exchange, acid base balance, nitrogenous waste excretion, and other metabolic transformations. They are one of the frst fsh organs to be exposed to heavy metals in the aquatic environment. The exposure of Oreochromis mossambicus to copper showed deleterious efects to normal fsh behaviours and varying degrees of gill damage when visualized under inverted light microscopy (stained with haematoxylin–eosin), scanning electron microscopy, and transmission electron microscopy. Abnormalities of the nucleus shape, swollen cells, lipid droplet deposition, and an increase in vacuolation on the afected gills were observed with the degree of damage associated with CuSO4 exposure concentration. CuSO4 exposure in O. mossambicus also gave various patterns of inhibitory efects on cholinesterase (ChE) depending on the concentration of exposure and the organs exposed. Copper exposure altered ChE activity extracted from the gills of O. mossambicus with 99.9% of inhibition at the highest exposure concentration of CuSO4 (20 mg/L). Hence, this study suggests the potential of this fsh to become a sentinel species that permits the detection of lower copper contamination levels.